(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
Interconnection of cities system transport problems, surrounding natural environment and territorial organization has been discussed by the example of Iranian Сity Gorgan. The role of transport flow of passengers is revealed and evaluated in the process of regional sustainable development.